Polymorphisms of the Thy1 (Thymocyte Differentiation Antigen 1) Gene in Candidate IPB D2 Chicken Line - Nensy Tri Putri; Sri Murtini; Niken Ulupi; Isyana Khaerunnisa; Cece Sumantri (Jurnal Ilmu Ternak dan Veteriner, 2022)
The Thy1 gene is a member of the immunoglobulin superfamily, which is found in many different animals. This gene encodes a Thy1 protein (CD90) which measures 25–37 kDa. Although the function of the Thy1 gene is unknown, it is thought to play a crucial role in the immunological response, particularly in the activation of T cells. The goal of this study was to find a variation in the Thy1 gene in IPB D2  chickens that might be utilized as candidates for immunoresistance genetic markers. A total of 123 samples from IPB D2 chickens consisting of 38 samples from IPB D2 G0 (basic generation) chickens and 85 samples from IPB D2 G2 (second generation) chickens were used in this study. PCR methods and direct-DNA sequencing were used in this study. Data analysis in this study consisted of genotype frequency, allele frequency, observed heterozigosity, expected heterozygosity, and Hardy-Weinberg equilibrium. The results of the study  discovered two SNPs on the intron (g.2139 CT and g.2542 AG). Four haplotypes were created by combining two SNPs. The g.2139 CTand g.2542 AG were polymorphic, but not in the Hardy-Weinberg equilibrium.